Natural history and outcome of aortic stenosis diagnosed prenatally. Issue 3 (March 1997) - Simpson, J. M.; Sharland, G. K.
Abstract : OBJECTIVE: To document the growth of the left heart structures and outcome of fetuses with aortic stenosis. DESIGN: Retrospective echocardiographic and clinical study. SETTING: Tertiary centre for fetal cardiology. PATIENTS: 27 consecutive fetuses with aortic stenosis. MAIN OUTCOME MEASURES: Survival of affected fetuses. Measurement of left ventricular end diastolic volume (LVEDV), aortic root diameter, and ejection fraction. RESULTS: Before 25 weeks' gestation, the LVEDV was normal or increased in all cases. In six of eight fetuses studied sequentially, the LVEDV fell across normal centiles. Initial ejection fraction was reduced in 23 fetuses (88%). Before 28 weeks' gestation, the aortic root was normal in all but one case, but after 29 weeks, 11 of 13 fetuses had values below the 50th centile. In two fetuses prenatal aortic valvoplasty was attempted, 10 babies had postnatal interventions, and there were six survivors. Biventricular repair was attempted in eight cases, of whom five survived. A first stage Norwood operation was performed in three babies, of whom one survived. The four fetuses with the highest aortic root z scores had successful biventricular repair. The two fetuses with initially normal ejection fractions survived. Successful biventricular repair was achieved even where the LVEDV was below the 5th centile. CONCLUSIONS: In aortic stenosis diagnosed prenatally, failure of growth of the left ventricle and aortic root often occurs. The outcome of affected fetuses is better than previously reported. Prenatal echocardiography may assist selection of suitable candidates for biventricular versus Norwood repair.